METTL14-Mediate the Biological Effects of EMT in Bladder Cancer Cells by Methylating SOX4 mRNA with m6A - Xie, Mengliang; Zhang, Huantao (Indian Journal of Pharmaceutical Education and Research, 2024)
Objectives Bladder Cancer (BC) is one of the most common malignant tumours of urinary system, with high rates of metastasis and mortality. Methyltransferase-like 14 (METTL14) is an RNA N6-adenosine methyltransferase that can affect the development of tumours by modifying RNA expression. The study aims to uncover the molecular mechanism and biological function of METTLI4 in BC. Materials and Methods qRT-PCR assays were employed METTL14 in BC cell lines. MeRIP-qPCR and RIP were used to verify that SRY-related high-mobility-group box 4 (SOX4) modification by m6A is a downstream target of METTL14. Results Biological experiments in vitro have demonstrated the biological function of METTL14 on BC cells. In the MGH-U3 cell lines, the expression of METTL14 was significantly down-regulated (p < 0.001), while the expression of SOX4 was significantly up-regulated (p < 0.01). Intervention of METTL14 expression can affect cell proliferation, migration, invasion, apoptosis, as well as the expression of EMT proteins in BC cell lines (p < 0.05). In addition, METTL14 can affect the biological functions of MGH-U3 cells and the expression of EMT proteins through the m6A modification of SOX4. Conclusion METTL14 overexpression inhibited the proliferation, migration, invasion, and promoted apoptosis in BC cells, and also downregulated the expression of EMT-related proteins, while these effects were abolished by silencing SOX2. This suggests that METTL14, through its influence on SOX4 m6A modification, plays a crucial role in regulating the biological functions of bladder cancer cells, indicating its potential as a therapeutic target for BC.
Keywords: METTL14; EMT; Bladder cancer; SOX4 mRNA; m6A